Catalytic Oxidation of Lignins into the Aromatic Aldehydes: General Process Trends and Development Prospects - Valery E. Tarabanko (International Journal of Molecular Sciences, 2017)
This review discusses principal patterns that govern the processes of lignins’ catalytic oxidation into vanillin (3-methoxy-4-hydroxybenzaldehyde) and syringaldehyde (3,5-dimethoxy-4-hydroxybenzaldehyde). It examines the influence of lignin and oxidant nature, temperature, mass transfer, and of other factors on the yield of the aldehydes and the process selectivity. The review reveals that properly organized processes of catalytic oxidation of various lignins are only insignificantly (10–15%) inferior to oxidation by nitrobenzene in terms of yield and selectivity in vanillin and syringaldehyde. Very high consumption of oxygen (and consequentially, of alkali) in the process—over 10 mol per mol of obtained vanillin—is highlighted as an unresolved and unexplored problem: scientific literature reveals almost no studies devoted to the possibilities of decreasing the consumption of oxygen and alkali. Different hypotheses about the mechanism of lignin oxidation into the aromatic aldehydes are discussed, and the mechanism comprising the steps of single-electron oxidation of phenolate anions, and ending with retroaldol reaction of a substituted coniferyl aldehyde was pointed out as the most convincing one. The possibility and development prospects of single-stage oxidative processing of wood into the aromatic aldehydes and cellulose are analyzed.